TAHFIDZ PROGRAM METHODS FOR DEVELOPING AL-QUR’AN LITERACY AMONG LOWER-GRADE STUDENTS - Tsaniyah, Azni Ifadatuts; Nisa, Faizatun; Setiyaningsih, Sri Isnani (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study addresses the issue of low Qur’anic literacy among lower-grade elementary and madrasah students despite the widespread implementation of tahfidz programs in educational institutions. The study aims to analyze and compare various tahfidz program methods in supporting the development of students’ Qur’anic literacy, including reading accuracy, tajweed, and pronunciation skills. This study employed a qualitative approach using library research methods. Data were collected from relevant scientific journals and academic literature and analyzed through content analysis techniques. The findings from the reviewed literature indicate that the talaqqi method is associated with improving reading accuracy, while the sima'i method supports early learning through listening and imitation. In addition, the muroja'ah and takrir methods contribute to strengthening memorization through repetition, whereas the tasmi' method is commonly used for evaluation and increasing students’ self-confidence. Overall, the reviewed studies suggest that integrating various tahfidz methods may provide broader support for the development of Qur’anic literacy than relying on a single method. This study implies the importance of applying varied and integrated tahfidz learning methods in elementary education.